Analysis of Legal Protection for Vehicle Owners in Cases of Confiscation of Trucks Used to Transport Illegal Timber (Study Decision Number: 170/Pid.B/Lh/2023/Pn Plk) - Singkarasi, Nalau; Winjaya Laksana, Andri (UNISSULA Semarang, 2024)
It is not uncommon for forest utilization to be misused by some people or in the form of corporations, these actions cause forest damage. Individuals or corporations encroach on forests by cutting them down, or by using heavy equipment rented through individuals or legal entities and then transported using vehicles such as trucks. What if the trucks that have been rented are misused to commit criminal acts of forest encroachment by the tenant, of course this needs to be studied further. In this study, the approach method used is: a normative legal approach or an approach through literature study. The research specification used is Descriptive Analytical, which is an effort to analyze and explain legal problems related to objects with a comprehensive and systematic description of everything related to the rights of truck owners in forestry crimes. The author believes that it is important to understand the legal basis and processes in handling cases of confiscation of trucks used to transport wood illegally.